2021
DOI: 10.2147/jpr.s277574
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ultrasound Therapy on the Management of Chronic Non-Specific Low Back Pain: A Systematic Review

Abstract: Non-specific chronic low back pain is the most common self-reported kind of musculoskeletal ache associated with substantial health and socioeconomic problem and responsible for most years lived with a disability as compared with any other medical condition. So treating chronic non-specific low back pain is one of the main problems faced among physical therapists in the rehabilitation area. The effects of ultrasound for patients with non-specific chronic low back pain remain unknown, however it is commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
1
12
0
3
Order By: Relevance
“…The A previous systematic review explained that UST evidence of chronic NSLBP had a small effect on improving low back function in the short term compared with placebo (Ebadi et al, 2014). Meanwhile, a recent systematic review that included 699 patients proved that UST was able to reduce visual analog scale scores in chronic NSLBP (Haile et al, 2021). UST is an electrophysical agent utilizing acoustic energy at a frequency of 1.0 -3.0…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The A previous systematic review explained that UST evidence of chronic NSLBP had a small effect on improving low back function in the short term compared with placebo (Ebadi et al, 2014). Meanwhile, a recent systematic review that included 699 patients proved that UST was able to reduce visual analog scale scores in chronic NSLBP (Haile et al, 2021). UST is an electrophysical agent utilizing acoustic energy at a frequency of 1.0 -3.0…”
Section: Discussionmentioning
confidence: 99%
“…The standard intervention that can be applied to NSLBP is a combination of electrotherapy (such as ultrasound therapy/UST) and exercise therapy techniques (such as stretching training) (Câmara-Gomes et al, 2022;Haile et al, 2021;Oliveira et al, 2018;Shiri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that hydrotherapy can positively affect pain, strength, muscle flexibility, performance, self-confidence, fitness, and stress reduction in disorders, such as LBP [10]. Furthermore, physiotherapy methods, including using ultrasound devices [12], Transcutaneous Electrical Nerve Stimulation (TENS) [21], and hot water packs [22], have been old and very common applications in reducing patients' back pain. Ultrasound and TENS devices, through surface waves and electrical stimulation with the help of a hot water bag, increase blood circulation in muscles and soft tissues, which is quite effective in improving the healing process and reducing the transmission of pain nerve commands [12,21].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Moreover, Bai et al, in a review and meta-analysis study, pointed to the positive benefits of water exercise [7]. In another review article, Haile et al reported that physiotherapy methods also effectively reduce LBP [12].…”
Section: Introductionmentioning
confidence: 99%